Cardiovascular Implications Due To Air Pollution: A Review Paper (International Journal of Food and Nutritional Sciences, 2022)
Particulate matter (PM) and gaseous pollutants like nitrogen dioxide and ozone make up air pollution. Coarse particles (PM10), fine particles (PM2.5), and ultrafine particles (PM100) are the three sizes of PM. We want to offer a unique overview of the scientific data from epidemiological and experimental research looking at the impact of outdoor air pollution on the cardiovascular system. According to a meta-analysis of epidemiological research, a 10g/m3 increase in long-term PM2.5 exposure was linked to an 11% increase in cardiovascular death. Long-term and short-term nitrogen dioxide exposure were both linked to an increase in cardiovascular mortality. As shown by early aortic and coronary calcification, exposure to air pollution and road traffic was linked to an elevated risk of arteriosclerosis. Myocardial infarction, stroke, and abrupt heart failure have all been linked to short-term increases in air pollution. Even when pollutant concentrations were below European limits, the danger was raised. Numerous experimental investigations have shown that air pollution induces a systemic vascular oxidative stress response, corroborating the findings from epidemiological studies. Endothelial dysfunction, monocyte activation, and certain proatherogenic alterations in lipoproteins are all caused by reactive oxygen species, which lead to plaque development. Furthermore, because of a rise in coagulation factors and platelet activation, air pollution promotes thrombus formation. Experiments have also shown that certain pollutants, such as combustion-derived PM2.5 and ultrafine particles, have greater detrimental cardiovascular effects. Cardiovascular disorders are exacerbated by air pollution. Promoting better air quality seems to be a new issue in the prevention of cardiovascular disease.